Lao People's Democratic Republic : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
Against the backdrop of generally sound policies and abundant natural resources, Lao P.D.R. has made impressive progress in developing its economy and reducing poverty. The key challenge going forward is to ensure that economic policy frameworks stay ahead of the curve to achieve sustainable and broad-based growth.